PENGARUH PERHATIAN DAN MOTIVASI ORANG TUA TERHADAP SIKAP BELAJAR SISWA DI KELAS XI PERHOTELAN SMK NEGERI 4 KOTA JAMBI - Rahmadenti, Tika Adis; Afrila, Diliza (Universitas Batanghari Jambi, 2022)
This study aims to determine (1) the effect of parental attention on student learning attitudes in class XI hospitality at SMK Negeri 4 Jambi City, (2) parental motivation on student learning attitudes in class XI hospitality at SMK Negeri 4 Jambi City, (3) the effect of parents' attention and motivation towards student learning attitudes in class XI hospitality at SMK Negeri 4 Jambi City. This type of research is a descriptive research method with two independent variables and one dependent variable. The population in this study is 117 people. The sampling technique used in this study is proportional random sampling, so 90 people were selected as research samples. Data collection techniques in this study is to distribute questionnaires to research respondents. The results showed that (1) the effect of parental attention on learning attitudes obtained a value of tcount > ttable (5.862 > 1.988). That is, parental attention has a significant effect on student learning attitudes in class XI hospitality at SMK Negeri 4 Jambi City, (2) the influence of parental motivation on learning attitudes obtained a value of tcount > ttable (6.004 > 1.988). That is, parental motivation has a significant effect on student learning attitudes in class XI hospitality at SMK Negeri 4 Jambi City, and (3) parental attention and motivation significantly affect student learning attitudes in class XI hospitality at SMK Negeri 4 Jambi City. This is based on the value of Fcount > Ftable (30,708 > 3.08), so it can be concluded that Ho is rejected.Keywords: Parents' Attention, Parents' Motivation, Learning Attitude